YgaE Regulates Out Membrane Proteins in Salmonella enterica Serovar Typhi under Hyperosmotic Stress - Min Wang; Ping Feng; Xun Chen; Haifang Zhang; Bin Ni; Xiaofang Xie; Hong Du (The Scientific World Journal)
Salmonella enterica serovar Typhi (S. Typhi) is a human-specific pathogen that causes typhoid fever. In this study, we constructed ΔygaE mutant and a microarray was performed to investigate the role of ygaE in regulation of gene expression changes in response to hyperosmotic stress in S. Typhi. qRT-PCR was performed to validate the microarray results. Our data indicated that ygaE was the repressor of gab operon in S. Typhi as in Escherichia coli (E. coli), though the sequence of ygaE is totally different from gabC (formerly ygaE) in E. coli. OmpF, OmpC, and OmpA are the most abundant out membrane proteins in S. Typhi. Here we report that YgaE is a repressor of both OmpF and OmpC at the early stage of hyperosmotic stress. Two-dimensional electrophoresis was applied to analyze proteomics of total proteins in wild-type strain and ΔygaE strain and we found that YgaE represses the expression of OmpA at the late stage of hyperosmotic stress. Altogether, our results implied that YgaE regulates out membrane proteins in a time-dependent manner under hyperosmotic stress in S. Typhi.